Upaya Meningkatan Kemampuan Berhitung Anak Usia Dini 5-6 Tahun Melalui Permainan Tebak Angka Menggunakan Bahan Recycle di Kober Al Barokah - Laila Hadiyana Ahmad; Elnawati Elnawati; Redi Awal Maulana (PT. Alahyan Publisher Sukabumi, 2025)
This research aims to improve the numeracy ability of early childhood ages 5-6 years through a guessing game using recycled materials at Kober Al Barokah. Numeracy is one of the important aspects in early childhood cognitive development that supports the understanding of basic mathematical concepts. This research uses the classroom action research method (PTK) which is carried out in two cycles, with each cycle covering the stages of planning, implementation, observation, and reflection. The subjects of the study were 20 children aged 5-6 years in Kober Al Barokah. Data was collected through observation, numeracy tests, and documentation. The guessing game is designed using recycled materials such as cardboard, bottle caps, and ice cream sticks that are modified into interactive learning media. The results of the study show that the application of the guessing game in a structured manner can improve children's numeracy skills. In the first cycle, children's numeracy increased from an average of 60% to 75%, and in the second cycle it increased to 90%. Children are more enthusiastic about learning, able to recognize numbers, count the number of objects, and understand the concept of simple addition. The conclusion of this study is that the guessing game using recycled materials is effective in improving early childhood numeracy skills as well as instilling awareness of the importance of using recycled materials.